1995
DOI: 10.1007/bf01281153
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of GTP cyclohydrolase I in the brain, adrenal gland, and liver of mice

Abstract: GTP cyclohydrolase I (GCH) is the first and rate-limiting enzyme for the biosynthesis of tetrahydrobiopterin (BH4), the cofactor of phenylalanine, tyrosine, and tryptophan hydroxylases, the enzymes that synthesize tyrosine, catecholamines (dopamine, noradrenaline, and adrenaline), and serotonin, respectively. We produced for the first time polyclonal antibody with highly sensitive immunoreactivity against an oligopeptide of rat enzyme, GEPERELPRPGA, by immunization of rabbits with the peptide conjugated to hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 39 publications
2
35
1
Order By: Relevance
“…An interesting connection between adrenal gland and brain 5-HT synthesis was made by Miller et al (1980), who demonstrated that brain tryptophan utilization was determined by the presence or absence of the adrenal gland. GTP cyclohydrolase is present in the adrenal gland, and this makes the tetrahydrobiopterin that is a necessary cofactor of the tyrosine, tryptophan, and phenylalanine hydroxylases (Nagatsu et al, 1995). Thus, there is potential for 5-HT to modify blood pressure through actions in the adrenal gland.…”
Section: E 5-hydroxytryptamine Presence and Function In The Adrenal mentioning
confidence: 99%
“…An interesting connection between adrenal gland and brain 5-HT synthesis was made by Miller et al (1980), who demonstrated that brain tryptophan utilization was determined by the presence or absence of the adrenal gland. GTP cyclohydrolase is present in the adrenal gland, and this makes the tetrahydrobiopterin that is a necessary cofactor of the tyrosine, tryptophan, and phenylalanine hydroxylases (Nagatsu et al, 1995). Thus, there is potential for 5-HT to modify blood pressure through actions in the adrenal gland.…”
Section: E 5-hydroxytryptamine Presence and Function In The Adrenal mentioning
confidence: 99%
“…Western Blotting-Antibodies were made against purified bovine TH (26), purified bovine AADC (23), and synthetic peptide for rat GCH (27). Monoclonal antibody against TPH was purchased from Oncogene.…”
Section: Generation Of a Targeted Mutation In 6-pyruvoyltetrahydropterinmentioning
confidence: 99%
“…The brains were dissected and sliced at 40 m, and their adrenal glands and kidneys, at 25 m, with a cryostat after having been rinsed with sucrose. Sections were pretreated with 0.5% hydrogen peroxide (H 2 O 2 ), blocked with 5% normal swine serum or 5% normal goat serum, and incubated with rabbit anti-TH serum (26), rabbit anti-AADC serum (26), rabbit anti-GCH serum (27) and mouse anti-TPH monoclonal antibody (Ab-1, 0nco-gene, Cambridge) diluted to 1:100,000, 1:20,000, 1:1000, and 1 ng/l respectively, followed by biotinylated goat anti-rabbit IgG or biotinylated anti-mouse IgG and avidin-biotin peroxidase complex (Vectastain ABC kit, Funakoshi). Then the sections were visualized by a reaction with 3,3Šˆ-diaminobenzidine tetrahydrochloride and 0.003% H 2 O 2 .…”
Section: Generation Of a Targeted Mutation In 6-pyruvoyltetrahydropterinmentioning
confidence: 99%
“…GTP-cylcohydrolase (GTPCH) is the rate-limiting enzyme in the pathway leading to the production of tetrahydrobiopterin, and cultured rat glioma cells 26 and cancer cell lines 27 produce the GTPCH enzyme, although glial cells in brain do not normally express the GTPCH gene. 28 Both clone 877 and clone 951 produce TH enzyme activity in either cultured rat glioma cells or cultured human U87 glioma cells (Table 1). There is a 5-to 8-fold higher level of TH gene expression in human cells, which are targeted with the HIRmAb, as opposed to TH gene expression in rat glioma cells, which are targeted with the TfRmAb.…”
Section: Th Gene Therapy Of Experimental Parkinson's Disease With Pegmentioning
confidence: 99%